2022
DOI: 10.1073/pnas.2025606119
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and grain-scale minor sulfur isotope data reveal complexities in the dynamics of Earth’s oxygenation

Abstract: Significance The permanent disappearance of mass-independent sulfur isotope fractionation (S-MIF) from the sedimentary record has become a widely accepted proxy for atmospheric oxygenation. This framework, however, neglects inheritance from oxidative weathering of pre-existing S-MIF–bearing sedimentary sulfide minerals (i.e., crustal memory), which has recently been invoked to explain apparent discrepancies within the sulfur isotope record. Herein, we demonstrate that such a crustal memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 72 publications
1
30
0
Order By: Relevance
“…Occasionally, big perturbations to the atmosphere, such as an LIP, might have lowered O 2 concentrations enough for sulfur isotope MIF to reoccur. Note that the above explanation for the cause of O 2 oscillations prior to 2.2 Ga is complicated by S-MIF data presented in Izon et al ( 11 ), which do not suggest the same O 2 variability found by Poulton et al ( 9 ).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Occasionally, big perturbations to the atmosphere, such as an LIP, might have lowered O 2 concentrations enough for sulfur isotope MIF to reoccur. Note that the above explanation for the cause of O 2 oscillations prior to 2.2 Ga is complicated by S-MIF data presented in Izon et al ( 11 ), which do not suggest the same O 2 variability found by Poulton et al ( 9 ).…”
Section: Discussionmentioning
confidence: 76%
“…Here, we use our time-dependent photochemical model to address the controversy of the reversibility of the oxic transition ( 9 , 11 ). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stratigraphic distributions of Δ 33 S data from the South African Kaapvaal (c core EBA-2; d core KEA-4) and Western Australian Pilbara (e cores T1-T3) cratons, whose discrepant interpretations have led to the emergence of conflicting models of atmospheric oxygenation. Each of the chronologically constrained lithostratigraphic columns follow those presented with the Δ 33 S data 22,25,30,32,33 , with the superimposed vertical grey bars illustrating the ±0.3‰ threshold for identifying S-MIF by Δ 33 S alone 25 . The lowermost horizontal blue band in c, d corresponds to the apparently sustained presence of massindependent sulfur isotope fractionation (S-MIF) within the Rooihoogte Formation (Ro(oi)) seen throughout the Carletonville area 22,25,30,37 , while others envisage an oscillatory trajectory whereby pO 2 repeatedly crossed the threshold necessary to resume S-MIF genesis [24][25][26] (Fig.…”
mentioning
confidence: 99%
“…1a-d). While inadequate age constraints and ambiguous stratigraphic correlations [22][23][24][26][27][28][29][30] currently prevent discrimination between these models (Supplementary Information), both interpretations are reliant on the assumption that sedimentary S-MIF chronicles contemporaneous atmospheric conditions. Again, this premise is not universally accepted and some contend that the operation of a so-called crustal memory effect (CME) decouples the MSI record from coeval atmospheric chemistry 16,[31][32][33] .…”
mentioning
confidence: 99%